UV and zero valent iron treatment of endosulfan - Gallardo, Susan M. (Animo Repository, 2008)
UV and ZVI treatment of stockpile endosulfan in water at lab scale was investigated. Results show the mechanism for UV treatment is free radical reaction. A decrease in concentration of 86% was obtained for both isomers but produced endosulfan ether. No significant change in the pH and chloride were observed. For ZVI treatment, the mechanism is by reductive dechlorination. A decrease in concentration of 64.73% for a-endosulfan and 81.86% for B endosulfan was obtained, a change in pH from 2 to 5. and chloride increase by 1.75 ppm was seen with no other forms of endosulfan found. For combined UV- ZVI treatment, both isomers decreased in concentration by 86%, an increase in pH. from 2 to 6, and dechlorination of 1.75 ppm resulted in the treated solutions. Toxicity analysis for UV treatment showed the solutions as toxic but non-toxic for ZVI and combined UV-ZVI treated solutions. Further tests still needs to be conducted to confirm toxicity and chloride results.